(untitled) (Research, Society and Development, 2022)
This study aimed to map the scope of scientific evidence on the therapeutic effects of cannabinoids on breast cancer. Methodological study to review the scientific literature in the bases: Scopus, PubMed and MEDline, being accessed through the CAPES/MEC Journal Portal and in the bases: Science Direct, Cochrane and Virtual Health Library. After testing and retesting using the operator Boolean connective AND, the following descriptors were applied to the databases: (therapeutic uses cannabis) AND (therapy) AND (breast cancer or breast neoplasms). The results found showed six studies, only one of the quantitative type and five of literature review that presented the integrative therapeutic use of cannabinoids and their benefits for the relief of symptoms. It was concluded that there is a lack of scientific evidence on the relief of symptoms and ways of using integrative cannabinoid therapy in breast cancer.